The Role of Mobile Phones in the Transmission of Methicillin-Resistant Staphylococcus aureus (MRSA) among the Students and Staff of the College of Health and Medical Technology/ Kufa in Najaf, Iraq - Oday Mitib Hadi (Journal of Global Pharma Technology, 2016)
Background: During every phone call the mobile phone, come into close contact with strongly contaminated human body areas with hands to hands, and hands to other areas like mouth, nose, and ears [10]. Mobile phones touch faces, ears, lips, and hands of different users thus they may be serves as reservoirs of different pathogens [11]. This study was designed to determine the role of the mobile phones in the transmission of methicillin-resistance Staph. aureus. Methodology: The cross-sectional study was done in the college of health and medical technology/ Kufa- Najaf- Iraq. Three hundred swab samples from mobile phones were collected from the students and staff of the college from November- 2015- February-2016 and divided into three groups categorized according to the site of collection (from the mobile phones) as follows: earpiece, keypad or touch screen, and mouthpiece. All samples were cultured, and the resulting isolates were identified and subjected to antimicrobial susceptibility test by standard procedures (Kirby-Bauer method).Methicillin-resistant Staph. aureus was detected by using polymerase chain reaction (PCR) based on mecA gene. Results: Keypad or touch screen was occupied the highest percentage (58.74%) of bacterial contamination among other regions i. e. earpiece (26.7%) and mouthpiece (14.83%).Coagulase-negative Staph. aureus was predominant (41.83%) bacterial genus among other Gram-positive genera. Other Gram-positive bacteria had different ratios; there were 28.37%, 19.71%, 8.65%, 0.96% and 0.048 for Micrococcus spp., Bacillus spp. Methicillin-sensitive Staph. aureus (MSSA), Methicillin-resistant Staph. aureus (MRSA), and Enterococcus faecalis, respectively. On the other hand, Gram-negative bacteria gave different percentages, ranging from 53.57% for E. coli to 3.57% for Salmonella spp. Molecular detection was revealed the presence of mecA gene in only two isolates of Staph. aureus. Conclusion: Mobile phones may serve as vehicles of transmission of methicillin-resistance Staph. aureus.Keywords: Mobile phones, Methicillin Resistant Staph. aureus, Meca gene.